ChemInform Abstract: Preparation and Reactions of 4‐Iodobutyl Pinacolborate. Synthesis of Substituted Alkyl and Aryl Pinacolboronates via 4‐Iodobutyl Pinacolborate Utilizing Tetrahydrofuran as the Leaving Group. Issue 40 (October 2015) - Murphy, Chris L.; Hall, Aaron; Roberts, Emily J.; Ryan, Matthew D.; Clary, Jacob W.; Singaram, Bakthan
Abstract The mild method offers significant improvement compared to previous procedures in terms of operational simplicity as well as costs and environmental impact of the reagents used.